Financial Management - Johnson, Robert W. (Boston: Allyn and Bacon, 1962)
The aim of this book is to provide a theoretical or conceptual framework that the financial manager can use to reach decisions in a dynamic economy.
Includes index
occ 16/01/2019
Loans
Keywords: Finance; Management; Financial management